Learning Methods and Scientific Approaches on Integrated Thematic Learning - Deni Setiawan; Erna Rokhimiya Putri; Arif Hidayat (Postgraduate, University of Mataram, 2023)
In the 2013 curriculum, elementary schools are carried out with integrated thematic learning. This study aims to analyze the integrated thematic learning activities of grade III. The research uses qualitative methods with a phenomenological approach. The research informant was one grade III teacher. The subjects in this study were 19 grade III students. Data was collected at SD Negeri 2 Soborejo using interviews, observations, and documentation. The data validity techniques used are the Credibility Test and the Confirmability Test. In researchers, a credibility test was carried out using increased persistence in research, triangulation techniques and member checks. The Confirmability Test is carried out using a journal to reflect on the data that has been collected. A scientific approach is applied in learning activities because the curriculum used is the 2013 Curriculum. Conclusion of the research, integrated thematic learning activities are carried out using several learning methods, according to the stage of the sequence of learning activities and learning principles Integrated thematic, then a scientific approach is applied in learning.